SGLT2i Inhibitor Therapy in the Management of Pulmonary Hypertension: A Literature Review - Dentino Wili Mahendra (Publikasi Indonesia, 2026)
Pulmonary hypertension (PH) is a complex, progressive condition marked by elevated pulmonary vascular resistance and artery pressure, often leading to right heart failure. Therapeutic options remain limited, especially for PH due to left heart disease (PH-LHD) and pulmonary arterial hypertension (PAH). Sodium—glucose cotransporter 2 inhibitors (SGLT2i), developed for diabetes, show cardiorenal benefits beyond glycemic control, suggesting a role in PH management. This narrative literature review synthesizes evidence on SGLT2i in PH, focusing on mechanisms, preclinical findings, and clinical outcomes. Systematic searches (PubMed, Scopus, ScienceDirect; 2020–2025) reveal SGLT2i modulate PH pathophysiology via mild osmotic diuresis; reduced inflammation and oxidative stress; improved endothelial function; inhibited vascular remodeling; and enhanced right ventricular function. Preclinical animal studies report lower pulmonary artery pressure and remodeling. Early clinical data from observational studies and heart failure trial sub-analyses indicate improved hemodynamics (e.g., pulmonary artery pressure, NT-proBNP) in PH patients, particularly PH-LHD. In conclusion, SGLT2i offer promise as adjunctive therapy for PH linked to left heart disease due to multimodal actions. Evidence remains preliminary from non-PH-specific trials; ongoing randomized controlled trials will clarify efficacy and safety for broader recommendation.